MODELING OF CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN FAST FOOD INDUSTRY - Sum Sochenda (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The main objectives of this paper were to examine the antecedent factors (i.e., quality of service, quality of food, quality of physical environment, fairness of price and brand image) that influenced customer satisfaction, and then assess the causal relationships between customer satisfaction and customer loyalty in the fast-food restaurant segment. By a convenience sampling approach and self-administered questionnaire method, the questionnaires of 480 were distributed to customers of 6 brand fast-food restaurants in Phnom Penh, Cambodia, and then having only 403 (=83.95%) of the total sample size usable for this study. In compliance with the structural equation modeling (SEM) techniques, the collected data were analysed with the statistical software SPSS 22.0 and AMOS 26 Graphics. Confirmatory factor analysis (CFA), moreover, was employed to verify the goodness-of-fit of data towards the model, indicator and composite reliability, and convergent and discriminant validity before running SEM. This study found that brand image was the most significant positive predictor to stimulate customer satisfaction, followed by quality of food and fairness of price, except the quality of service and quality of physical environment. The level of customer loyalty, in turn, was influenced by customer satisfaction. The findings truly provided the requisite contributions to the existing theories and managerial implications particularly relevant to determining the success factors within the fast-food restaurant context.